Gold, Bitcoin, and Central Banks in the 21st Century: The New Dynamic - Griffin, Carroll Howard (International Journal of Finance, 2025)
This paper examines how gold and Bitcoin have changed in terms of value and function in the context of the central banking system in the 21st century. Over the past decades, central banks have held gold as one of their primary reserve assets, given its stability, relative rarity, and traditional status as an inflation hedge and financial crisis buffer. However, with the advent of Bitcoin, central banks now have the opportunity to hold a new asset, one that has been compared to “digital gold”. On one hand, Bitcoin revolutionizes the monetary system because it is decentralized, has built in scarcity, and serves as a store of value. However, on the other hand, Bitcoin has traditionally been highly volatile, suffered from regulatory issues, and possesses a relatively short history; all of which hinder Bitcoin from becoming more accepted among central banks. Factors are discussed that affect central bank reserve management: the enduring role of gold, Bitcoin as an additional reserve, and the growing significance of central bank digital currencies. It is argued that while it remains unclear whether central banks will fully integrate Bitcoin into current reserves, its acceptance thus far may impact the decision of global monetary systems regarding incorporating digital technologies alongside more conventional assets, such as gold.